Death of Francis A. Walker (Quarterly Journal of Economics, 1897)
Journal Article Death of Francis A. Walker Get access The Quarterly Journal of Economics, Volume 11, Issue 2, January 1897, Pages 210–211, https://doi.org/10.1093/qje/11.2.210 Published: 01 January 1897